Effect of filamentous algae in a microalgal-bacterial granular sludge system treating saline wastewater: Assessing stability, lipid production and nutrients removal. (June 2022) - Cao, Jinhua; Chen, Fanzhen; Fang, Zheng; Gu, Yue; Wang, Hao; Lu, Jingfang; Bi, Yanmeng; Wang, Shaopo; Huang, Wenli; Meng, Fansheng
Highlights: Filamentous algae were built on the saline microalgal-bacterial granular sludge. Filamentous algae remarkably enhanced the stability of MBGS granules. Lipid content of MBGS was five times than AGS under 5% salinity. Filamentous Leptolyngbya and Geitlerinema were dominant algae in granules. MBGS granules exhibited better overall performance for N & P removal. Abstract: In this study modified microalgal-bacterial granular sludge (MBGS) was constructed and employed to compare the performance for treating 1%-5% saline wastewater with aerobic granular sludge (AGS). Filamentous algae were found to flourish at 1% salinity when nutrients were temporarily restricted to low level (COD 0, N 10 mg/L, P 0.5 mg/L). A significant improvement of granule stability was detected as the integrity coefficients of MBGS was only 0.12–0.24 rather than 0.19–0.48 of AGS under 1%-5% salinities, which reduced the risk of particle disintegration. Filamentous algae including Leptolyngbya and Geitlerinema occupied 91.2% of identified algae, and were beneficial for enhancing the biomass content and lipid production to about 1.27–1.37, 3.1–5.0 times than AGS. The MBGS had best nitrogen and phosphorus removal efficiencies of 93.4% and 64.6% at 1% salinity, and showed higher resistance to 3%-5% salinities. This study could provide meaningful information for using this modified MBGS technology in practice.